2018
DOI: 10.1177/1365712718783427
|View full text |Cite
|
Sign up to set email alerts
|

Evidentiary instructions improve mock juror assessment of feature-comparison evidence

Abstract: Feature-comparison evidence has been introduced in court without sufficient scientific validation and has been at the heart of numerous miscarriages of justice. Juror assessment of such evidence and the efficacy of evidentiary instructions were examined through a mock jury experiment with case reports featuring either central or peripheral feature-comparison evidence. In a case-control design (N = 174), the test group was exposed to an evidentiary instruction about the ear print evidence presented in the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Research on the usefulness of such an intervention is mixed. In terms of generally improving jurors’ decision making related to evidence and different types of expert testimony, some research suggests that specialized and/or case-specific jury instructions may improve jurors’ decision making (Ribbers & Henneberg, 2018), whereas other research casts doubt on their usefulness (Bornstein & Greene, 2011; Eastwood & Caldwell, 2015; Jones et al, 2020; Papailiou et al, 2015). The eyewitness literature has largely found that when presented with jury instructions highlighting the limitations of eyewitness testimony or the variables that can affect identification reliability, jurors tend to become more skeptical of the eyewitness evidence overall, regardless of the evidence’s strength or weakness (Dillon et al, 2017; Papailiou et al, 2015).…”
Section: Improving Juror Comprehension Of Forensic Testimonymentioning
confidence: 99%
“…Research on the usefulness of such an intervention is mixed. In terms of generally improving jurors’ decision making related to evidence and different types of expert testimony, some research suggests that specialized and/or case-specific jury instructions may improve jurors’ decision making (Ribbers & Henneberg, 2018), whereas other research casts doubt on their usefulness (Bornstein & Greene, 2011; Eastwood & Caldwell, 2015; Jones et al, 2020; Papailiou et al, 2015). The eyewitness literature has largely found that when presented with jury instructions highlighting the limitations of eyewitness testimony or the variables that can affect identification reliability, jurors tend to become more skeptical of the eyewitness evidence overall, regardless of the evidence’s strength or weakness (Dillon et al, 2017; Papailiou et al, 2015).…”
Section: Improving Juror Comprehension Of Forensic Testimonymentioning
confidence: 99%